Nonlinear structures & systems. proceedings of the 38th IMAC, a conference and exposition on structural dynamics 2020 /: proceedings of the 38th IMAC, a conference and exposition on structural dynamics 2020. Volume 1 ([2021]) - Unknown
No abstract available